1992
DOI: 10.1038/sc.1992.139
|View full text |Cite
|
Sign up to set email alerts
|

Results of the combined treatment of paediatric intraspinal tumours

Abstract: In this article 98 patients with paediatric intraspinal tumours are presented. All were evaluated according to their ages, sex, signs and symptoms. The patients also had radiological and histopathological studies; and the results of surgical, physical medicine and rehabilitation and of radiotherapy are discussed and compared with the results of patients reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
9
0
3
Order By: Relevance
“…Dincer et al in a retrospective review reported urinary dysfunction in 40.8% of children with spinal tumours 15. Bladder dysfunction is, however, rare in children with brain tumours and this is reflected in the few clinical reviews reporting this association.…”
Section: Discussionmentioning
confidence: 99%
“…Dincer et al in a retrospective review reported urinary dysfunction in 40.8% of children with spinal tumours 15. Bladder dysfunction is, however, rare in children with brain tumours and this is reflected in the few clinical reviews reporting this association.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature state that micturition disorders were a common symptom found in children with spinal tumors. 22,23 Bladder dysfunction should be suspected in patients with spinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ključni oblici liječenja u ranom stadiju bolesti uključuju kiruršku intervenciju, kemoterapiju i radioterapiju te rehabilitacijske postupke 9 . Liječenje se sastoji primarno od ciklusa polikemoterapija u trajanju od 12 do 24 tjedana, a svrha im je smanjiti aktivnost malignih stanica i uništiti mikrometastaze te samim time povećati mogućnost izvođenja radikalnoga kirurškog zahvata s negativnim resekcijskim rubom, što znači da je rub resekcije čist od tumorskih stanica.…”
Section: Mogućnosti Liječenja I Prognozeunclassified
“…Prijeoperacijskom pripremom nastoji se spriječiti i ublažiti odstupanje od fiziološkog te skratiti vrijeme oporavka. Fizioterapeut provodi tehnike respiratorne terapije, nastoji očuvati mobilnost zglobova i mišićnu snagu kroz aktivne, pasivne i asistirane pokrete te educira pacijenta i njegovu obitelj u svrhu poboljša-nja kvalitete života 1,9,14 . Ciljevi su poslijeoperacijske fizioterapije i rehabilitacije poboljšanje stanja preostalog zdravlja otkrivanjem čimbenika rizika koji mogu pogoršavati opće stanje i kvalitetu života onkoloških bolesnika, prevencija nastanka komplikacija i onesposobljenja putem radnoterapijskih programa i edukacije, programi podrške u vidu logopedskog tretmana, psihološke podrške te protetičke i ortotičke opskrbe 14 .…”
Section: Simptomi Klinička Slika I Dijagnostikaunclassified
See 1 more Smart Citation